2020
DOI: 10.1101/2020.08.07.240762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Organization of Midget and Parasol Ganglion Cells in the Human Retina

Abstract: The functional organization of diverse retinal ganglion cell (RGC) types, which shape the visual signals transmitted to the brain, has been examined in many species. The unique spatial, temporal, and chromatic properties of the numerically dominant RGC types in macaque monkey retina are presumed to most accurately model human vision. However, the functional similarity between RGCs in macaques and humans has only begun to be tested, and recent work suggests possible differences. Here, the properties of the nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…Morphological studies of the complete primate retina, on the other hand, describe a similar variety in ganglion cell types as found in the non-primate retina with at least 17 morphologically identified types [11,[20][21][22][23]. However, functional studies of these non-foveal ganglion cell types in non-human primates have been limited to a set of 7 types [14,[24][25][26][27][28][29] and only midget and parasol cells have been recorded in human retina [18,19]. Additional physiological assessment of the human retina on the level of individual cells is anecdotal [30,31].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Morphological studies of the complete primate retina, on the other hand, describe a similar variety in ganglion cell types as found in the non-primate retina with at least 17 morphologically identified types [11,[20][21][22][23]. However, functional studies of these non-foveal ganglion cell types in non-human primates have been limited to a set of 7 types [14,[24][25][26][27][28][29] and only midget and parasol cells have been recorded in human retina [18,19]. Additional physiological assessment of the human retina on the level of individual cells is anecdotal [30,31].…”
Section: Introductionmentioning
confidence: 91%
“…The foveal region consists almost exclusively of four retinal ganglion cell types, the ON and OFF parasol cells, and the ON and OFF midget cells [8][9][10], which account for 50-70% of all ganglion cells in the primate retina [11]. Functional studies using human and non-human primates have often focused on these four most abundant retinal ganglion cell types [12][13][14][15][16][17][18][19]. Morphological studies of the complete primate retina, on the other hand, describe a similar variety in ganglion cell types as found in the non-primate retina with at least 17 morphologically identified types [11,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the manifold may aid in translating our understanding of the macaque retina to the human retina, an important goal for biomedical research. Recent work 13,14 has shown that the receptive field properties of the four numerically dominant RGC types (ON and OFF parasol and midget) are similar to those of their macaque counterparts. To test whether light responses in the human retina fall within the range observed across many macaque retinas, the manifold location of a single human retina was identified using the three operations described above (averaging, approximation, optimization).…”
Section: Manifold Generalizes To a Novel Recordingmentioning
confidence: 99%
“…The foveal region consists almost exclusively of four retinal ganglion cell types, the ON and OFF parasol cells, and the ON and OFF midget cells [ 8 – 10 ], which account for 50–70% of all ganglion cells in the primate retina [ 11 , 12 ]. Functional studies using human and non-human primates have often focused on these four most abundant retinal ganglion cell types [ 13 – 20 ]. Morphological and transcriptomic studies of the complete primate retina agree that midget and parasol cells are the dominating cell types, but these studies describe a similar variety in the remaining ganglion cell types as found in the non-primate retina with at least 12 additional types [ 11 , 12 , 21 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and transcriptomic studies of the complete primate retina agree that midget and parasol cells are the dominating cell types, but these studies describe a similar variety in the remaining ganglion cell types as found in the non-primate retina with at least 12 additional types [ 11 , 12 , 21 – 24 ]. However, functional studies of these non-foveal ganglion cell types in non-human primates have been limited to a set of 7 types [ 15 , 25 – 30 ] and only midget and parasol cells have been characterized in human retina [ 19 , 20 ]. Additional physiological assessment of the human retina on the level of individual cells is anecdotal [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%